Sustainable built heritage: maintenance management appraisal approach - Kayan, Brit (Emerald, 2019)
Purpose: Sustainability encapsulated economic, environmental and societal parameters. Without exception, these parameters also conforms the efficiency and increasingly importance of sustainable maintenance management for built heritage. However, there is less attention to the appraisal approach for maintenance management of built heritage, twinned with inconsistent and impractical assessment upon their maintenance strategies. With the aim to support sustainability, the purpose of this paper is to give an insight to the question on how the maintenance management appraisal approach practically determines and ultimately substantiates the decision-making process that promotes sustainable built heritage, based on current scenarios and practices in Malaysia. Design/methodology/approach: Maintenance management appraisal for sampling of built heritage enables assessment of efficiency of maintenance and repair during maintenance phase based on survey (questionnaires) and statistical analysis. Findings: It recognises the importance of maintenance management appraisal in achieving efficiency and underpinning rationale decision making for maintenance strategies and service quality (SERVQUAL). Practical implications: It must be emphasised that maintenance management appraisal is not confined to built heritage, and can be applied to any types and forms of property. The decision made as a result of its utilisation is practically support sustainable repair. Social implications: The implementation of this appraisal highlights the efficacy of maintenance strategies and SERVQUAL that may be adopted. Originality/value: The paper is a rigorous appraisal of maintenance management of built heritage. This appraisal relays the “true” sustainable built heritage, contextualised within maintenance strategies and SERVQUAL that consequently allows rationale in achieving sustainable development. © 2019, Emerald Publishing Limited.